PENGARUH AUTHENTIC LEADERSHIP TERHADAP INNOVATIVE WORK BEHAVIOR MELALUI WORK-LIFE BALANCE SEBAGAI MEDIASI - Aprilia, Yasinta; Rahmat, Adi; Munthe, Richa Afriana (Jurnal Daya Saing, 2026)
Innovative Work Behavior is an employee's innovative work behavior that is the main focus of human resource management research due to its crucial role in generating new ideas, implementing creative solutions, and driving organizational change. The influence of Authentic Leadership on Innovative Work Behavior is the main focus of this study. This research aims to analyze the influence of Authentic Leadership on Innovative Work Behavior with Work-Life Balance as a mediating variable. This research utilizes a quantitative approach with a causality design, with the study population covering all 104 State Civil Apparatus (ASN) in the Indragiri Hilir Regency Education Office. The data collection technique used a questionnaire. The research data were analyzed using the Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) with Smart PLS 3.2.9 software. The findings of this research identify that Authentic Leadership has a positive and significant impact on Innovative Work Behavior, both directly and through the mediation of Work-Life Balance. In addition, Work-Life Balance has also been shown to have a positive and significant impact on Innovative Work Behavior.